Can Reliance On Multiple Performances Measures (RMPM) Boost Employee Productivity Through Employee Loyalty? - Marthalia Putri; Yuliansyah Yuliansyah (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
The aim of the study isto investigate the extent to whichreliance on multipleperformances measures (RMPM)leverages employee productivity. Assuming that thisrelationship exists when an employee has a high level of loyalty, we survey nurses anddoctors in severalhealthcare organisationsin Bandar Lampung.Eighty-two returnedsurveys yielded usable datasets from 76 respondents. Analysing data with SPSS 19.0, wefound that RMPM can leverage employee productivity through employee loyalty, but wefound no direct effect of RMPM onemployee productivity.This study enriches researchon management accounting and on employee behaviour in the service sector, in particularin health care organizations.